2021
DOI: 10.1017/s0305000921000337
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic influence in simultaneous and early sequential bilingual children: a meta-analysis

Abstract: Although cross-linguistic influence at the level of morphosyntax is one of the most intensively studied topics in child bilingualism, the circumstances under which it occurs remain unclear. In this meta-analysis, we measured the effect size of cross-linguistic influence and systematically assessed its predictors in 750 simultaneous and early sequential bilingual children in 17 unique language combinations across 26 experimental studies. We found a significant small to moderate average effect size of cross-ling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 77 publications
4
64
3
Order By: Relevance
“…It is for instance obvious that a “bilingual is not two monolinguals in one person” (Grosjean, 1989 ). There is cross-linguistic influence at play in bilingual development (Müller and Hulk, 2001 ) that is attested in many morphosyntactic domains in 2L1 and eL2 (e.g., Schmitz et al, 2012 ; Scherger, 2016 ; for a meta-analysis see van Dijk et al, 2021 ). This interaction of languages within a bilingual individual is “part and parcel of bilingual development” (van Dijk et al, 2021 , p. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is for instance obvious that a “bilingual is not two monolinguals in one person” (Grosjean, 1989 ). There is cross-linguistic influence at play in bilingual development (Müller and Hulk, 2001 ) that is attested in many morphosyntactic domains in 2L1 and eL2 (e.g., Schmitz et al, 2012 ; Scherger, 2016 ; for a meta-analysis see van Dijk et al, 2021 ). This interaction of languages within a bilingual individual is “part and parcel of bilingual development” (van Dijk et al, 2021 , p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…There is cross-linguistic influence at play in bilingual development (Müller and Hulk, 2001 ) that is attested in many morphosyntactic domains in 2L1 and eL2 (e.g., Schmitz et al, 2012 ; Scherger, 2016 ; for a meta-analysis see van Dijk et al, 2021 ). This interaction of languages within a bilingual individual is “part and parcel of bilingual development” (van Dijk et al, 2021 , p. 1). However, it is unclear whether early bi- or multilingual speakers are native speakers of two or more languages (Wilkinson, 2020 , p. 285).…”
Section: Introductionmentioning
confidence: 99%
“…A negative cross-linguistic influence (also called cross-linguistic transfer/interference), defined as "deviation from the norms of either language which occur in the speech of bilinguals as a result of their familiarity with more than one language" (Weinreich, 1968), has been robustly demonstrated in the acquisition of L2/SL in simultaneous and sequential bilingual children (e.g., Zdorenko and Paradis, 2008;Blom et al, 2012). A recent meta-analysis which evaluated cross-linguistic influence and its predictors in 750 simultaneous and early sequential bilingual children (aged 4;0-10;0) in 17 unique language combinations across 26 experimental studies confirmed the presence of crosslinguistic influences in bilingual morphosyntactic acquisition (see Van Dijk et al, 2021).…”
Section: Factors Affecting Child Heritage Language (Hl) Acquisitionmentioning
confidence: 93%
“…Alternatively, studies showed that child HL speakers diverge from their monolingual peers in this domain. Some researchers attribute these divergences to cross-linguistic influences (for a detailed overview on cross-linguistic influence in child bilingualism see Serratrice, 2013;Van Dijk et al, 2021), while some studies found that cross-linguistic influences did not affect the HL acquisition of morphosyntax, suggesting that language-external factors shape child HL development (e.g., Daskalaki et al, 2019Daskalaki et al, , 2020Rodina et al, 2020). Cross-linguistic influences and languageexternal factors might not be mutually exclusive and shape HL development together (Daskalaki et al, 2019(Daskalaki et al, , 2020Van Dijk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation